2019
DOI: 10.36076/ppj/2019.22.53
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Exercise Therapy and Manipulation on Sacroiliac Joint Dysfunction: A Randomized Controlled Trial

Abstract: Background: The sacroiliac joint dysfunction (SIJD) has been found to be the primary culprit for lower back pain (LBP), but it is still overlooked and treated as LBP. There are no guidelines or appropriate therapeutic protocols for SIJD. Thus, there is a need for an effective treatment strategy for SIJD. Objective: To compare exercise therapy (ET), manipulation therapy (MT), and a combination of the 2 (EMT) in terms of their effectiveness in treating SIJD. Study Design: A comparative, prospective, single-blind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 0 publications
0
29
0
1
Order By: Relevance
“…The implication is that a systematic biomechanical assessment of the fascial system can lead to applications of myofascial treatments, such as Fascial Manipulation ® , that can restore the correct density of the hyaluronan between the layers of the thoracolumbar fascia and in adjacent fascial layers and, in this way, re-establish correct basal tension, receptor transmission and sacroiliac function, with a consequent reduction in perceived pain [ 13 ]. Furthermore, the possibility of rapidly decreasing pain around the SIJ can ostensibly improve patient management, allow for better tolerance of other treatments and permit the early application of pain-free exercise programs to establish more efficient movement patterns [ 1 , 9 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The implication is that a systematic biomechanical assessment of the fascial system can lead to applications of myofascial treatments, such as Fascial Manipulation ® , that can restore the correct density of the hyaluronan between the layers of the thoracolumbar fascia and in adjacent fascial layers and, in this way, re-establish correct basal tension, receptor transmission and sacroiliac function, with a consequent reduction in perceived pain [ 13 ]. Furthermore, the possibility of rapidly decreasing pain around the SIJ can ostensibly improve patient management, allow for better tolerance of other treatments and permit the early application of pain-free exercise programs to establish more efficient movement patterns [ 1 , 9 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sacroiliac joint dysfunction (SIJD) generally refers to pain in the lower back due to abnormal sacroiliac joint movement, either from hypomobility or hypermobility. It is considered to be the principal cause in up to 40% of low back pain cases [ 1 ]. The sacroiliac joint (SIJ) is an amphiarthrosis, 75% of which is formed by a synovial joint and the remaining part by fixed fibrocartilaginous elements.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the high prevalence of sacroiliac dysfunction, there are no therapeutic protocols for this syndrome. It has been previously considered as a potential contributor to lower back pain but, according to scholars, there are few studies that have compared the effectiveness of the different therapeutic techniques [7].…”
Section: Introductionmentioning
confidence: 99%
“…This condition is clinically referred to as SIJ subluxation [4]. Pathological bone destruction and traumatic fracture and dislocation require surgery [15][16][17][18], while SIJ pain without a speci c cause is usually treated with manipulations [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…There are several common manipulations, including manipulation of hip and knee exion (MHKF), manipulation of oblique pulling (MOP), and manipulation of lower limb hyperextension (MLLH). A large number of studies have reported that manipulations have a good effect on the treatment of SIJ subluxation [19][20][21]. Different types of SIJ subluxation require different manipulations [22,23].…”
Section: Introductionmentioning
confidence: 99%